ASSESSMENT OF GENETIC DIVERSITY IN GERMPLASM COLLECTION OF LINSEED (Linum usitatissimum L.) - CHHAYA ATRI; HITESH KUMAR (The Bioscan, 2024)
Molecular characterization of 72 linseed (Linum usitatissimum L.) germplasm accessions was carried out using 30 ISSR markers. Out of 350 amplified alleles 344 alleles showed polymorphism among evaluated germplasm accessions. Private bands and % heterozygosity were high in breeding material generated at PAU, Ludhiana and exotic germplasm collected from different breeding centres worldwide. There was 78.15±7.85 avarage % ISSR polymorphism resided among these 72 accessions, highest 89.68 % among breeding and exotic accessions, 76.79 % and 56.45 % Indian and flax varieties respectively. Also these two groups had high mean heterozygosity in comparison to Indian and flax varieties. Clustering based on Neighbor-Joining (NJ) cluster analysis wherein the genotypes were clustered into eight major clusters lacking clear grouping among clusters. Pair wise population Nei genetic distance and identity was highest between Indian and flax varieties (0.094) and lowest between breeding and exotic lines (0.017). Accessions constitutes breeding material and exotic collection were more diverse than Indian and flax varieties. These findings are useful for selection for identification of suitable diverse parental genotype for hybridization in linseed cultivars development programme.